PENEGAKKAN HUKUM UNTUK PENGELOLAAN SAMPAH DI KOTA BEKASI - Sri Hutomo (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Waste management is currently still an unresolved problem. This research aims to examine problems in waste management in Bekasi City. This research is doctrinal/normative legal research with a statutory approach. Data was collected by literature study, then analyzed qualitatively. There are several laws and regulations that have a correlation with waste management in Indonesia, namely Law No. 18 of 2008 concerning Waste Management, Law no. 32 of 2009 concerning Environmental Protection and Management and several other laws. Law enforcement in waste management refers to 3 legal systems which are a combination of components, namely structure, substance and culture. Apart from that, related to law enforcement in waste management, it can be studied from 2 sides, namely preventive and repressive law enforcement. Law enforcement in waste management is also an embodiment of the government and local governments in implementing the principles of Good Environmental Governance with the aim of raising public awareness of a good and healthy environment.